Human papilloma virus and nasopharyngeal carcinoma: pathology, prognosis, recurrence and mortality of the disease - Atighechi, S.; Mirvakili, S.A.; Sheikhha, M.H.; Baradaranfar, M.H.; Dadgarnia, M.H.; Behniafard, N.; Ahmadpour Baghdadabad, M.R. (Experimental Oncology, 2014)
Background: One of the malignant tumors among head and neck cancers is nasopharyngeal carcinoma. Many studies consider human papilloma virus (HPV) as a cause for nasopharyngeal carcinoma. Methods: 41 paraffin-wax-embedded block samples were examined to detect HPV DNA and its subtype’s presence by polymerase chain reaction. The recurrence, prognosis and survival were evaluated for an average of 48 months. Results: HPV DNA was positive in 9 patients (22%). The overall recurrence rate was 75% in HPV negative patients and 11% in HPV positive ones. The mortality rate in HPV negative and positive patients was 37.5% and 0%, respectively. Conclusion: HPV type 18 and 16 were the most common subtypes. Also, it can be implied that patients which are HPV positive had better prognosis and also less recurrence. Key Words: human papilloma virus, nasopharyngeal cancer, polymerase chain reaction, prognosis, recurrence.